Saving Viable Businesses : The Effect of Insolvency Reform - Klapper, Leora (World Bank, Washington, DC, 2012)
The 2008 financial crisis and consequent rise in corporate insolvencies highlight the clear need for efficient bankruptcy systems to liquidate unviable firms and reorganize viable ones and to do so in a way that maximizes the proceeds for creditors, shareholders, employees, and other stakeholders. This note summarizes the empirical literature on the effect of insolvency reforms on economic and financial activity. Overall, research suggests that effective reforms increase timely repayments, reduce the cost of credit, and lower the rate of liquidation among distressed firms.